2005
DOI: 10.1093/chromsci/43.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Analysis of 2,4-D in Soil Samples by Modified Soxhlet Apparatus Using HPLC with UV Detection

Abstract: The 2,4-dichlorophenoxy acetic acid (2,4-D) is used as a systemic herbicide to control broadleaf weeds in wheat, corn, range land/pasture land, sorghum, and barley. In this study, a fast and efficient method is developed by selection of modified extraction apparatus and high-performance liquid chromatography (HPLC)-UV conditions for the determination of 2,4-D in soil samples. The method is applied to the study of soil samples collected from the agricultural field. The herbicide is extracted from soil samples b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The figures of merit of the Soxhlet method developed in the presented study for the determination of 2,4-D amine salt in water, sediment, and soil samples have been compared with other reported techniques [8,24]. Details of the relevant results of the methods and that of this study are provided in Tables 2 and 3.…”
Section: Comparison Of the Proposed Methods With Similar Literature R...mentioning
confidence: 99%
See 3 more Smart Citations
“…The figures of merit of the Soxhlet method developed in the presented study for the determination of 2,4-D amine salt in water, sediment, and soil samples have been compared with other reported techniques [8,24]. Details of the relevant results of the methods and that of this study are provided in Tables 2 and 3.…”
Section: Comparison Of the Proposed Methods With Similar Literature R...mentioning
confidence: 99%
“…The proposed method involves minimum labor and requires a short extraction time when compared to standard/tradition method. The performances of the developed technique were compared with that of the previously reported techniques of Kashyap et al [8] and Atalay and Hwang [24] in terms of relative recovery and regression coefficient (R 2 ). The findings confirmed that the developed technique is found to be comparable in terms of percent recoveries.…”
Section: Comparison Of the Proposed Methods With Similar Literature R...mentioning
confidence: 99%
See 2 more Smart Citations
“…High-performance liquid chromatography (HPLC) is general and popular for the analysis of drug and pesticide in biological samples [ 8 , 9 ]. Some HPLC methods have been established for the determination of 2,4-D residues in vegetables, fruits [ 10 ] and environmental samples [ 11 , 12 ], but only a few studies have been carried out for biological samples [ 13 , 14 ]. There is only limited data with respect to 2,4-D pharmacokinetic properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%